A study on assessment of effects of electronic gadgets on mental and physical health among medical students in Central India - Marskole, Priyesh; Yadav, Rashmi; Sethia, Soumitra; Parmar, Sachin; Bhagora, Rinku; Parihar, Leena (International Journal Of Community Medicine And Public Health, 2021)
Background: Human race has witnessed enormous technological advancements especially in last few decades. Electronic gadgets are part of everyday lives of all individuals in all age groups. On one side they make our lives easier and convenient and on the other side their excessive usage is harmful. These gadgets effect physical as well as mental health. Present study was conducted to see the effects of electronic gadgets on physical and mental health of medical students. Methods: A cross-sectional study was conducted among MBBS students of Central India. Students who were present on the time of data collection were included in the study. For the study, data collection tool was a pre-designed, semi structured questionnaire, collected data was compiled in excel sheet and relevant analysis was done. Results: About 70% have habit of waking up between 6 to 8 AM. 95.5% of subjects were using smartphones, 61.5% of subjects using laptop/computer. 58% were spending time with gadgets less than 4 hours while 6.5% were spending more than 10 hours. We found out that 54% had ophthalmic health effects and 46.5% participants accepted feeling anxious, irritated or restless without their gadgets. The study revealed health problems of participants as headache (30%), migraine (1%), depression (7%) and other problems like backache, weakness, joint pain and others. Conclusions: The current and exiting data so far suggest that gadget have definite risk and adverse effects on the health of the general population.